Exploration of Surgical Patients’ Perspectives of Peri-Operative Nursing Care at the Regional Hospital, Bolgatanga - Adugbire, A.B (University of Ghana, 2015)
The purpose of this study was to explore surgical patients‘ perspective of perioperative nursing care at the Regional Hospital, Bolgatanga. The study was guided by Perioperative Surgical Home (PSH) as Microsystems health care model. The study employed a qualitative explorative descriptive design. Purposive sampling technique was used to recruit participants. The data was saturated with 15 participants aged between 23 and 65 years. All the interviews were audio-taped and transcribed verbatim. Data was analysed using the principles of thematic content analysis. Three major themes emerged from the study: preoperative perspectives, intraoperative perspectives and postoperative perspectives of care. These themes were consistent with the PSH Model. Also, additional theme that emerged was faith in God. Nurses helped to assess and triage patients to identify specific cases for urgent surgery. Nurses provided reassurance, counseling and prehabilitation and physical care to patients but failed to take patients‘ medical history. Nurses contributed effectively to ensure patients‘ safety and performed infection prevention to some extent during surgery but poorly managed patients‘ pain. Some patients sustained minor injuries as a result of poor usage of theatre equipments. Nurses provided inadequate information to patients throughout the perioperative period. Nurses exhibited poor communication attitude toward patients and poorly managed their wounds resulting in wound infection. Also, patients encountered high cost of care and nurses failed to visit patients at home after discharge. It was recommended that health care providers should involve patients in planning care. They should conduct physical assessment and review items used in the theatre
Thesis (MPh) - University of Ghana, 2015